Indicators for evaluating trends of air humidification in arid regions under circumstance of climate change: Relative humidity (RH) vs. Actual water vapour pressure (ea). (February 2021) - Wei, Qi; Xu, Junzeng; Liao, Linxian; Yu, Yanmei; Liu, Weixuan; Zhou, Jing; Ding, Yimin
Highlights: Trends of air humidification in arid regions are evaluated by RH and ea . RH tend to give a misleading in evaluating the trends of wetting or drying. ea is more consistent with the precipitation changes and suitable for trending analyses of air humidification. Abstract: The trend of wetting or drying is an important metric of regional and global climate change. Based on daily meteorological data during 1951–2018 from 10 stations in arid regions of North China, the performances of two indicators, relative humidity (RH) and actual water vapour pressure (ea ), in evaluating the trends of air humidification are investigated. Results show that annual RH decreases by 0–0.10% yr −1 during the past decades in almost all (90%) stations, whereas annual ea presents increasing trends in 40% of stations and decreasing trends in the other 60% stations. Therefore, contrasting results are observed in the trends of air humidity reflected RH and ea . Specifically, stations getting significantly drying as indicated by RH, it is tend to getting less drying or even wetting as indicated by ea . These results suggest that it tend to give a misleading conclusion with the trends of RH as indicator in evaluating the trends of regional or global wetting or drying, due to the reduction in RH caused by the accompanying temperature rising under global warming. The other indicator ea is more consistent with the precipitation changes, and suitable for trending analyses of air humidification under such circumstance. Further researches should be done in a larger scale arid region and in different seasons, to investigate the differences in the trends of air humidification indicated by RH and ea, and discuss the response of the changes of wetting or drying to the varied meteorological factors.